The source of income in South African income tax law and the inward and outward structuring of investments into and out of South Africa - Swanepoel, Etienne Roderick (Centre for Law and Society, 2024)
South Africa will shortly be a full member of the international community. This will result in both inward and outward investment. The South African income tax system is · based on the source of income. There is a limited reliance on the residence principle. It is essential to understand the scope of the source principle in both inward and outward investment. This thesis attempts to discuss these issues. It is a fascinating part of tax planning which will become more and more prevalent over time. Brief reference is made to the jurisprudential basis for income tax as also a comparative survey of other jurisdictions where reliance is placed on the source principle.